A Pragmatic Analysis of Interactional Functions in Fostering Social Interaction Among Business English Communication Students - Suraj, Safitri Rahmadani; Amin, Fatimah Hidayahni; Kamariah, Andi (Journal of Excellence in English Language Education, 2026)
The purpose of this study is to examine how university students use interactional functions to build solid social interactions within their student organization. This research applied a qualitative descriptive method using observation and semi-structured interviews with six members of the organizational student, HMPS BE Creative in the English Department. The data were analyzed using a thematic approach. The findings reveal that students frequently used various interactional functions such as greetings, expressions of praise, empathy, support, and feedback to maintain closeness and emotional bonding. These interactional functions were also linked with elements of Social Interdependence Theory, including positive interdependence, individual accountability, promotive interaction, social skills, and group processing. The study highlights how students’ daily conversations reflect not only their task coordination but also their care, emotional intelligence, and efforts to create a supportive organizational culture. This research contributes to the understanding of how language functions strengthen social relationships in academic environments.